An in vivo N-15 NMR Study of agropine synthesis in transformed root cultures of Nicotiana tabacum - Ford, Y; Ratcliffe, R; Robins, R (2000)
The biosynthesis of the opine agropine in transformed Nicotiana tabacum L. root cultures was studied using in vivo 15N nuclear magnetic resonance (NMR) spectroscopy. Roots were incubated with [15N]ammonium and/or [15N]nitrate, and the incorporation of the label into agropine, conjugated polyamines, γ-aminobutyric acid (GABA), glutamate (Glu), glutamine (Gln) and nicotine was monitored by NMR. The largest labelled pool was agropine in cells grown on a 15N-enriched medium and its synthesis was maintained, to the detriment of the Gln pool, under conditions of nitrogen (N) starvation. These observations indicate that the synthesis of agropine is not tightly regulated and that it represents a significant sink for carbon (C) and N in the plant. The addition of α-naphthaleneacetic acid (NAA) and kinetin to the growth medium caused de-differentiation of the root cultures and perturbation of secondary N metabolism. The amount of agropine relative to Gln increased but the total accumulation of agropine decreased, in part because of the increase in the synthesis of conjugated polyamines. These results show that agropine biosynthesis perturbs both primary and secondary N metabolism, and that the perturbation differs according to the culture conditions and the imposed stress.